Where Have All Tech Layoffs Gone? A Model of Two Worker Types with Outsourcing - Sugata Marjit; Gouranga G. Das (Center for Economic Studies and ifo Institute (CESifo), 2023)
The flourishing of IT-sector and IT-enabled services has led to emergence of different activities by leaps and bounds thanks to proliferation of Virtual plaform-based transactions, and E-commerce. However, massive layoffs started in 2022, as all tech giants encountered revenue declines amidst supply chain issues, inflation, Ukraine war, leading to deflation and fears of recession squeezing consumer and business spending. This has happened across the globe. In the context of the countries supplying low-wage labor (skilled wage in Indian Silicon Valley at Bengaluru is lower than that in the Californian Silicon Valley), similar episodes unfolded but to a different extent. The evidence suggests that layoffs in developing economies like India is much less than that in the US with limited impact on Indian industry despite severe global downturn. Jobs and hiring will move out of the developed markets to these emerging markets with cost advantages owing to lower salaries, as with low demand, drive to cutdown costs will induce firms to outsource some operations outside while focusing on core functions provided the cost of outsourcing is not too high. In this paper, we build a model to show how contraction in demand for IT-enabled works will determine how much of works to be completed in the US (home) and the remainder to be sourced out to say, India (abroad). We identify the conditions under which switching from pure domestic production to outsourcing using hired foreign workers will happen. We show that in both cases of perfectly competitive homogeneous product as well as in case of differentiated goods oligopoly scenarios that the hiring ceases drastically in the home while the outsourced workers will not suffer to a large extent. Home bears the burden of adjustment due to the sheer cost disadvantages of the home.
Keywords: F11; F16; J63; O19; 330; outsourcing; layoffs; IT-enabled services; wage inequality; market structure